Effective fucoxanthin production in the flagellate alga Poterioochromonas malhamensis by coupling heterotrophic high-cell-density fermentation with illumination - Jin, Hu; Guo, Yufen; Li, Yanhua; Chen, Baofeng; Ma, Haiyan; Wang, Hongxia; Wang, Lan; Yuan, Danni (Frontiers in Bioengineering and Biotechnology, 2022)
The unicellular flagellate algae Poterioochromonas malhamensis is a potential fucoxanthin-rich resource for sustainable and cost-effective fucoxanthin production. Light and nutrients are critical regulators for the accumulation of fucoxanthin in P. malhamensis. In this study, the maximum fucoxanthin yield of 50.5 mg L-1 and productivity of 6.31 mg L-1 d-1 were achieved by coupling high-cell-density fermentation with illumination. It was found that the combined use of organic and inorganic nitrogen (N) nutrition could improve the fucoxanthin yield as single inorganic or organic N had limitation to enhance cell growth and fucoxanthin accumulation. White light was the optimal light quality for fucoxanthin accumulation. Under white light and a moderate light intensity of 150 μmol m-2 s-1, the highest biomass concentration and fucoxanthin content reached 32.9 g L-1 and 1.56 mg g-1 of dry cell weight (DCW), respectively. This is the first study on effective fucoxanthin production in P. malhamensis by integrating illumination with high-cell-density fermentation, which paved the way for further development of P. malhamensis as a potential source for commercial fucoxanthin production.